2022
DOI: 10.13057/biodiv/d230150
|View full text |Cite
|
Sign up to set email alerts
|

The enrichment process and morphological identification of anaerobic fungi isolated from buffalo rumen

Abstract: Abstract. Agustina S, Wiryawan KG, Suharti S, Meryandini A. 2021. The enrichment process and morphological identification of anaerobic fungi isolated from buffalo rumen. Biodiversitas 23: 469-477. Anaerobic fungi are one of the microbes that have an important role in rumen fiber degradation because they can produce cellulase enzymes and penetrate feed particles. Nevertheless, few studies were performed to test the potential of anaerobic fungi in Indonesia. Therefore, the present study was carried out to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…CYR and F4 were closely related to Neocallimastix frontalis isolate SK. This was in accordance with the results of morphological analysis previously carried out by Agustina et al (2022) that the isolates of buffalo rumen anaerobic fungi had the same morphological characteristics as Piromyces sp., Caecomyces sp., and Neocallimastix. It showed that molecular identification could be carried out to clarify and confirm the morphological identification results because according to Edwards et al (2017), morphological identification alone is not enough to determine genera and species of anaerobic fungi.…”
Section: Molecular Identificationsupporting
confidence: 92%
See 2 more Smart Citations
“…CYR and F4 were closely related to Neocallimastix frontalis isolate SK. This was in accordance with the results of morphological analysis previously carried out by Agustina et al (2022) that the isolates of buffalo rumen anaerobic fungi had the same morphological characteristics as Piromyces sp., Caecomyces sp., and Neocallimastix. It showed that molecular identification could be carried out to clarify and confirm the morphological identification results because according to Edwards et al (2017), morphological identification alone is not enough to determine genera and species of anaerobic fungi.…”
Section: Molecular Identificationsupporting
confidence: 92%
“…From the morning until the afternoon, the buffalo were grazed and fed grass or legumes, while at night until the morning the buffalo were put in the cage and fed with rice straw. The anaerobic fungi used were isolates F1, F2, F3, F4, and F5 from buffalo rumen by Agustina et al (2022). The isolates were maintained using Orpin media containing antibiotics and incubated at 39°C for 3 days before molecular identification (Jin et al 2011).…”
Section: Isolates and Fungi Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that each fungus isolated from the fecal specimens of mountain goats had white colonies, different diameters, and very slow growth. Previous studies have also shown that AGF has a very slow growth rate, longer than 15 days [34]. Considering the colony diameter measurements, the order of size can be listed as Neocallimastix , Piromyces , and Caecomyces [34].…”
Section: Resultsmentioning
confidence: 99%
“…Morphological identification is a method that can be used to determine the species of anaerobic gut fungi [23,33,34]. The morphological identification of the AGF isolated from goat rumen was made using genus-level identification keys [25].…”
Section: Growth and Morphological Characterizationmentioning
confidence: 99%